Hacking macrophage-associated immunosuppression for regulating glioblastoma angiogenesis. (April 2018) - Cui, Xin; Morales, Renee-Tyler Tan; Qian, Weiyi; Wang, Haoyu; Gagner, Jean-Pierre; Dolgalev, Igor; Placantonakis, Dimitris; Zagzag, David; Cimmino, Luisa; Snuderl, Matija; Lam, Raymond H.W.; Chen, Weiqiang
Abstract: Glioblastoma (GBM) is the most lethal primary adult brain tumor and its pathology is hallmarked by distorted neovascularization, diffuse tumor-associated macrophage infiltration, and potent immunosuppression. Reconstituting organotypic tumor angiogenesis models with biomimetic cell heterogeneity and interactions, pro-/anti-inflammatory milieu and extracellular matrix (ECM) mechanics is critical for preclinical anti-angiogenic therapeutic screening. However, current in vitro systems do not accurately mirror in vivo human brain tumor microenvironment. Here, we engineered a three-dimensional (3D), microfluidic angiogenesis model with controllable and biomimetic immunosuppressive conditions, immune-vascular and cell-matrix interactions. We demonstrate in vitro, GL261 and CT-2A GBM-like tumors steer macrophage polarization towards a M2-like phenotype for fostering an immunosuppressive and proangiogenic niche, which is consistent with human brain tumors. We distinguished that GBM and M2-like immunosuppressive macrophages promote angiogenesis, while M1-like pro-inflammatory macrophages suppress angiogenesis, which we coin "inflammation-driven angiogenesis." We observed soluble immunosuppressive cytokines, predominantly TGF-β1, and surface integrin (αv β3 ) endothelial-macrophage interactions are required in inflammation-driven angiogenesis. We demonstrated tuning cell-adhesion receptors using an integrin (αv β3 )-specific collagen hydrogel regulated inflammation-driven angiogenesis through Src-PI3K-YAP signaling, highlighting the importance of altered cell-ECM interactions in inflammation. To validate the preclinical applications of our 3D organoid model and mechanistic findings of inflammation-driven angiogenesis, we screened a novel dual integrin (αv β3 ) and cytokine receptor (TGFβ-R1) blockade that suppresses GBM tumor neovascularization by simultaneously targeting macrophage-associated immunosuppression, endothelial-macrophage interactions, and altered ECM. Hence, we provide an interactive and controllable GBM tumor microenvironment and highlight the importance of macrophage-associated immunosuppression in GBM angiogenesis, paving a new direction of screening novel anti-angiogenic therapies.